Heavy Load of Intestinal Fluke in a Four-Year-Old Child with Severe Acute Malnutrition: A Case Report - Deka, Sangeeta; Kalita, Deepjyoti; Hazarika, Naba Kumar (Journal of Laboratory Physicians, 2022)
Fasciolopsiasis, a food-borne intestinal parasitosis, occurs focally, and remains a significant public health problem in endemic areas. However, due to the wide spectrum of clinical presentation and unclear diagnosis or even misdiagnosis, it often goes unreported. The correlation between trematode infection and malnutrition is also often debated. We report a case of heavy infection of Fasciolopsis buski in a 4-year-old girl with severe acute malnutrition (SAM). The patient presented with a passage of many adult worms per stool following the consumption of some herbal concoction. A wet mount of the stool revealed ova of Fasciolopsis buski. She was treated successfully with praziquantel and food supplements. It raises the possibility of unidentified cases in this region and necessitates more extensive studies in the targeted population. This will also help raise awareness of fasciolopsiasis among clinicians, especially in vulnerable populations such as malnourished children.
Keywords: trematode infections; Fasciolopsis buski; malnutrition; children